(untitled) (Libellarium: journal for research in the field of information and related sciences, 2023)
Purpose. The aim of the paper is to describe the activities undertaken by Dubrovnik Libraries during and after the Croatian War of Independence to preserve their heritage collections. The intention is also to present plans for possible future challenges as well as to compare the conditions, resources and equipment available in the 1990s and in the present. Approach/methodology. The paper shows the degree of damage to the Library collections through an in situ case study, the basic data on how evacuation was approached, the organisation of work in crisis conditions, the storage of collections during the war period and then the relocation to the new building. The paper was based on primary sources, including first-hand accounts by the former Library Director Mrs Urban and interviews with older or retired librarians, and secondary sources such as the official report by a paper conservationist who conducted the inspection of damaged library materials in situ, newspaper articles, books, periodicals, doctoral thesis, emergency plan and measures etc. The research for this paper also enabled cooperation between librarians and conservators, as well as finding, scanning and archiving valuable historic library documents, which will be, as a result, available to any future researchers and for posterity. Findings. The paper presents a valuable experience of how endangered cultural heritage was protected in the past and offers contemporary insights into improving the methods of storing, preventive protection and transporting books and archive materials. To avoid previous mistakes, Dubrovnik Libraries developed the crisis response plan with emergency measures in 2020, while in the previous years numerous new resources and equipment had been put into place. Value. The paper gives an overview of a thirty-year long process of caring for heritage collections and it presents perspectives from both librarians and conservators. It outlines the way new resources – human, financial and technological – were used after the war to repair the damage and prevent anything similar from occurring in the future. Hopefully, this paper will raise awareness among cultural institutions and serve as a valuable aid in the practice of crisis management as well as preventive care.